Thermodynamic Analysis of an Innovative Cold Energy Storage System for Auto-Cascade Refrigeration Applications - Zhenzhen Liu; Jingde Jiang; Zilong Wang; Hua Zhang (Energies, 2023)
The cooling capacity needed by ultra-low temperature apparatus cannot be reached economically with a single vapor compression refrigeration cycle due to the constraint of the high compressor pressure ratio. The auto-cascade refrigeration cycle is a good alternative. In this work, a novel concept that applies the principle of the auto-cascade refrigeration cycle to store cold energy is conducted. The environment-friendly refrigerants of R600a/R290/R170 zeotropic mixtures are used to study the performance of the modified auto-cascade refrigeration cycle (MACRC) as an alternative for cold-energy applications. The simulation results show that a cooling capacity of 500 W can be provided below −60 °C. The mixture with a mass fraction of 0.25/0.35/0.40 yields a COP of 0.695 and an exergy efficiency of 0.262 at −66 °C. The performance of the MACRC system was investigated at an ambient temperature of 20 to 40 °C for indoor small-scale applications. It is concluded that the performance would be improved by decreasing the ambient temperature. The results of the work should be helpful for the design and optimization of auto-cascade systems.